Differences in technical performance of heading between men and women football players in FIFA World Cup 2022™ and FIFA Women`s World Cup 2023™ matches - Peek, K.; Georgieva, J.; Serner, A.; Orest, F. (Journal of Science and Medicine in Sport, 2024)
Introduction: Heading is a football-specific skill that can determine match results in Association Football, with headers being the second most efficient goal scoring technique, following kicks during free play. In the 2022 UEFA Women`s European Championship, 28% of all goals were scored from a header, and 19% of all goals in the 2020 UEFA Men`s European Championship. It has been estimated that the mean number of headers per player per match is 2.7 and 5.0 headers in boys and men`s football compared with 2.3 and 4.8 headers in girls and women`s football. There is limited heading incidence data in professional women`s football and while studies exploring some aspects of technical proficiency of heading during match play exist in men, there is paucity of such data in women.